Characterization of therapeutic proteins by cation exchange chromatography-mass spectrometry and top-down analysis - Rachel Liuqing Shi; Gang Xiao; Thomas M. Dillon; Margaret S. Ricci; Pavel V. Bondarenko (Taylor & Francis Group, 2020)
Recently, cation exchange chromatography (CEX) using aqueous volatile buffers was directly coupled with mass spectrometry (MS) and applied for intact analysis of therapeutic proteins and antibodies. In our study, chemical modifications responsible for charge variants were identified by CEX-UV-MS for a monoclonal antibody (mAb), a bispecific antibody, and an Fc-fusion protein. We also report post-CEX column addition of organic solvent and acid followed by mixing at elevated temperatures, which unfolded proteins, increased ion intensity (sensitivity) and facilitated top-down analysis. mAb stressed by hydrogen peroxide oxidation was used as a model system, which produced additional CEX peaks. The on-line CEX-UV-MS top-down analysis produced gas-phase fragments containing one or two methionine residues. Oxidation of some methionine residues contributed to earlier (acidic), some to later (basic) eluting peaks, while oxidation of other residues did not change CEX elution. The abundance of the oxidized and non-oxidized fragment ions also allowed estimation of the oxidation percentage of different methionine residues in stressed mAb. CEX-UV-MS measurement revealed a new intact antibody proteoform at 5% that eluted as a basic peak and included paired modifications: high-mannose glycosylation and remaining C-terminal lysine residue (M5/M5 + K). This finding was confirmed by peptide mapping and on-column disulfide reduction coupled with reversed-phase liquid chromatography - top-down MS analysis of the collected basic peak. Overall, our results demonstrate the utility of the on-line method in providing site-specific structural information of charge modifications without fraction collection and laborious peptide mapping.